ANALISIS KEMAMPUAN LITERASI MATEMATIKA SISWA SD NEGERI 54 PONTIANAK - Sulisti, Hidayu; Janah, Roikhatul (Program Studi Pendidikan Guru Madrasah Ibtidaiyah STAINU Purworejo, 2023)
Mathematical literacy is the ability to understand, use and interpret numbers and mathematical concepts, which is an important skill for every student to be a master. Mathematical literacy is important because it transcends cultural differences and economic inequality. The goal is to see the world through mathematical eyes, and the emphasis is on higher-order thinking, the development and application of general problem-solving skills rather than basic mathematical skills. The approach used in this research is a qualitative approach with a descriptive method. Based on the research results, it was found that students at SD Negeri 54 Pontianak had skills in solving and formulating problems with a high percentage, namely 70%. Students have the skills to explain solutions and interpret conclusions, the percentage is 47.5%. Meanwhile, the aspect of applying mathematical concepts or procedures obtained a percentage of 47.8%.